2020
DOI: 10.3390/land9050168
|View full text |Cite
|
Sign up to set email alerts
|

Who Remains When Professional Farmers Give up? Some Insights on Hobby Farming in an Olive Groves-Oriented Terraced Mediterranean Area

Abstract: Many land use systems in Mediterranean sloping areas risk abandonment because of nonprofitability, while their hydro-geological stability depends on an appropriate management. However, who are the land managers? What are their practices? Our research on the traditional olive groves of the Monte Pisano (Tuscany, Italy) reveals for the first time the quantitatively important role of hobby farmers as land managers in the area. We used a three-step-method: first, a database was constructed using several data sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
2
9
0
1
Order By: Relevance
“…This was reflected in our results, which showed that farmers considered the non-monetary benefits of farming as important as the monetary benefits. In line with Milone and Ventura [ 14 ], Pinto-Correia et al [ 50 ], Gennai-Schott et al [ 51 ], Gillespie and Mishra [ 52 ], and Howley [ 53 ], we found that, overall, the primary benefits of farming included working from home and on family-owned farmland. This indicated a strong sense of place and belonging and a feeling of attachment to the farm, the location where farmers were born and where their families and intimate childhood friends live.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was reflected in our results, which showed that farmers considered the non-monetary benefits of farming as important as the monetary benefits. In line with Milone and Ventura [ 14 ], Pinto-Correia et al [ 50 ], Gennai-Schott et al [ 51 ], Gillespie and Mishra [ 52 ], and Howley [ 53 ], we found that, overall, the primary benefits of farming included working from home and on family-owned farmland. This indicated a strong sense of place and belonging and a feeling of attachment to the farm, the location where farmers were born and where their families and intimate childhood friends live.…”
Section: Discussionsupporting
confidence: 89%
“…This indicated a strong sense of place and belonging and a feeling of attachment to the farm, the location where farmers were born and where their families and intimate childhood friends live. Living in a rural community with good social and environmental conditions was also found to be a benefit in attracting and retaining farmers in other studies [i.e., 50 , 51 , 54 ].…”
Section: Discussionmentioning
confidence: 68%
“…Examples of young male interviewees involved in farming but not perceiving it in terms of an important source of income are in line with phenomena described in the literature as "lifestyle farming" or "hobby farming", associated with small-scale and non-commercial agricultural activity, in the latter case also something done in somebody's spare time. It characterises rural residents (both local and newcomers from towns or cities) who are fond of living in the countryside and are willing to take care of the rural landscape and provide land stewardship (Gennai-Schott et al 2020). This is also typical among rural young adults in Northern Ireland, who often perceive farming, regardless of its economic viability, as a way of remaining physically and emotionally connected to previous generations of the farming family, as well as their place of origin (Stockdale and Ferguson 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Newcomer farmers often have no prior experience or generational ties to agriculture (Monllor i Rico and Fuller 2016: 534–537), resulting in inadequate access to land, local knowledge, and networks or policy support (EIP-AGRI Focus Group 2016: 15; Eistrup et al 2019). Lifestyle-led farmers tend to lack a farmer identity and consider farming a nonprofit or recreational activity, and so scholars and authorities often dismiss them as “hobbyists” or “unofficial” farmers (Sutherland et al 2019: 481; Gennai-Schott et al 2020: 4). However, they engage in agricultural practices in areas that have been abandoned by professional farmers (Gennai-Schott et al 2020) or maintain amenity values on the urban fringe after retirement (Song et al 2022).…”
Section: Conceptualizing Spatial and Social Lifestyle Mobilitymentioning
confidence: 99%